Fuzzy sets in ultrametric space - Мінаєв, Ю. М.; Філімонова, О. Ю.; Вінник, Д М.; Мінаєва, Ю. І.; Апонасенко, Д. В. (Problems of Informatization and Control, 2009)
The questions of presentation fuzzy variables, given in the manner of the interval with the assessed membershiр function, in the form p-adic number are discussed. Shown that р-adic base allows in the sufficient measure to take an uncertainty into account and avoid arbitrariness, which exists in the standart determination of membershiр functions